2018
DOI: 10.22159/ajpcr.2018.v11i10.19439
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Potential of Polysaccharide Isolated From Methanolic Extract of Tinospora Cordifolia Stem Bark

Abstract: Objective: Investigation of the antioxidant efficacy of a novel polysaccharide isolated from the methanolic extract of Tinospora cordifolia stem bark with reference to its action as free radical scavengers using in vivo and in vitro approaches was performed in the study.Methods: Lipid peroxidation (TBARS), superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) levels were determined with and without polysaccharide treatment in the cell lines and breast and liver tissues. 7, 12- Dimethylbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This analysis indicated that the anticancer potentials of this extract may be attributed to these major phytochemicals, and hence, the individual compound was isolated and studied for their anticancer property. There are several studies reporting the ability of plant extracts and plant-derived compounds to inhibit cell proliferation and induce apoptosis in breast cancer cells [14][15][16][17]. Plant extracts and plantderived bioactive molecules have been found to regulate and control the enhanced or uncontrolled cancer cell proliferation by specific modulation frequencies, targeting expression of genes associated with .…”
Section: Discussionmentioning
confidence: 99%
“…This analysis indicated that the anticancer potentials of this extract may be attributed to these major phytochemicals, and hence, the individual compound was isolated and studied for their anticancer property. There are several studies reporting the ability of plant extracts and plant-derived compounds to inhibit cell proliferation and induce apoptosis in breast cancer cells [14][15][16][17]. Plant extracts and plantderived bioactive molecules have been found to regulate and control the enhanced or uncontrolled cancer cell proliferation by specific modulation frequencies, targeting expression of genes associated with .…”
Section: Discussionmentioning
confidence: 99%
“…Tinospora cordifolia is commonly used in medicine where all the plant parts have curative property for certain diseases [5]. T. cordifolia exhibited properties such as antiinflammatory, anti-allergic, anti-stress [6], antidiabetic, antispasmodic, and anticancer [7]. T. cordifolia has a wide array of bioactive principles such as Berberine, Choline, Tembetarine, Magnoflorine, Tinosporin, Palmetine, Isocolumbin, Aporphine alkaloids, Jatrorrhizine, Tetrahydropalmatine [8][9][10], Tinocordifolioside, Cordioside, Cordifolioside, Syringin, Cordifolioside A, B, C, D, and E [11,12], β-sitosterol, δ-sitosterol, and Giloinsterol [13,14].…”
Section: Introductionmentioning
confidence: 99%